(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Highlighting disconcertingly higher incidence of early childhood malnutrition induced deficiencies and diseases concomitantly higher morbidity and mortality amongst children impairing their capacities and capabilities to learn, earn and grow, the article elucidated the need for establishing micro-food processing units at the village and town level for covering up this deficiencies in time effectively by processing ,preparing, and delivering packaged food items of cereals, millets and animal products to expecting mothers and children at their thresholds. The article provides deeper insight into the causes and consequences of nutritious deficiencies and related infirmities in children across states in India .The core purpose of the paper is to accentuate the need for promoting and leveraging the potential of micro food processing units for making available, accessible and affordable processed nutritious food at local level using local talent, knowledge and resources .The study highlights the need for adopting two pronged strategy to counter undernutretion in childhood ; proper and timely counselling of young married couples through mass awareness campaign on balanced nutritious diet and creating a supply chain for making available nutritious food items conveniently.